A dynamic computational network model for the role of nitric oxide and the myogenic response in microvascular flow regulation. (10th July 2018) - Liu, Yien; Buerk, Donald G.; Barbee, Kenneth A.; Jaron, Dov
Abstract: Objectives: The effect of NO on smooth muscle cell contractility is crucial in regulating vascular tone, blood flow, and O2 delivery. Quantitative predictions for interactions between the NO production rate and the myogenic response for microcirculatory blood vessels are lacking. Methods: We developed a computational model of a branching microcirculatory network with four representative classes of resistance vessels to predict the effect of endothelium‐derived NO on the microvascular pressure‐flow response. Our model links vessel scale biotransport simulations of NO and O2 delivery to a mechanistic model of autoregulation and myogenic tone in a simplified microcirculatory network. Results: The model predicts that smooth muscle cell NO bioavailability significantly contributes to resting vascular tone of resistance vessels. Deficiencies in NO seen during hypoxia or ischemia lead to a decreased vessel diameter for all classes at a given intravascular pressure. At the network level, NO deficiencies lead to an increase in pressure drop across the vessels studied, a downward shift in the pressure‐flow curve, and a decrease in the effective range of the autoregulatory response. Conclusions: Our model predicts the steady state and transient behavior of resistance vessels to perturbations in blood pressure, including effects of NO bioavailability on vascular regulation.